LAYANAN READERS’ ADVISORY DALAM MEWUJUDKAN LAYANAN REFERENSI YANG PRIMA PADA PERPUSTAKAAN - Irva Yunita; Reza Nawafella Alya parangu (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
This research discusses how reader's advisory services create excellent reference services in libraries. This study uses a qualitative research design with data collection using literature. The readers' advisory service is a user-oriented service to assist users in choosing the best works and according to the needs of these users according to the librarian's knowledge. So that in this readers' advisory service librarians have extensive knowledge about the many collections and needs of users. From this research it can be seen that readers' advisory services are services that support the creation of excellent reference services. However, to create a readers' advisory service, a librarian is needed who is willing to always learn so that he can find collections that suit the needs of users.